PERBANDINGAN TINGKAT KEBUGARAN JASMANI ANTARA SISWA SEKOLAH PAGI DENGAN SEKOLAH SIANG (STUDI PADA SISWA KELAS VIII SMPN 1 BALONG PANGGANG DAN SMP UDKP KEDAMEAN, GRESIK) - SETYO NUGROHO, WAHYU (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Generally, Penjasorkes is executed at morning until noon, like a learning activity in SMPN 1 Balong Panggang that executed at  the first and second period (07.00-08.20) and third and fourth period (08.20-10.05), with a fresh condition, so the learning activity can run optimally. While on the afternoon school at SMP UDKP Kedamean, learning is executed at afternoon until evening, that is at third and fourth period (13.40-14.50) and fifth and sixth period (15.15-16.25), with hot condition and have polluted. Learning condition will affect to the students’ activities. In the morning, students tend to be more energetic, while in the afternoon, students tend to be  lazy to do physical activities. The aims of this research are: 1) To find out the difference of physical fitness level of students between morning school students and afternoon school students in SMPN 1 Balong Panggang and SMP UDKP Kedamean, Gresik. 2) To find out what is the best whether physical fitness level of morning school students and afternoon school students. The type of this  research is comparative research. Sample collection in this research uses a cluster random sampling method. To measure the students physical fitness level, this research uses TKJI (Physical Fitness Test of Indonesia), data analysis uses Mann Whitney test. Based on the data calculation result obtained: average score from TJKI test for morning school students is 15.38 (medium category). While the average score for afternoon school students is 13.38 (poor category). Based on the data analysis and discussion, Mann-Whitney Test shows that significant score (0.000) is smaller than alpha score (5%) or 0.05. So Ha is accepted and Ho is rejected.  Thus, there is significant difference on physical fitness level between morning school students (SMPN 1 Balong Panggang) and afternoon school students (SMP UDKP Kedamean). It means that morning school students have better physical fitness than afternoon school students with average quarrel 2. Keywords: Physical fitness level, morning school students and afternoon school students.